JNK-dependent intestinal barrier failure disrupts host-microbe homeostasis during tumorigenesis - Zhou, Jun; Boutros, Michael (Proceedings of the National Academy of Sciences of the United States of America, 2020)
In all animals, the intestinal epithelium forms a tight barrier to the environment. The epithelium regulates the absorption of nutrients, mounts immune responses, and prevents systemic infections. Here, we investigate the consequences of tumorigenesis on the microbiome using a Drosophila intestinal tumor model. We show that upon loss of BMP signaling, tumors lead to aberrant activation of JNK/Mmp2 signaling, followed by intestinal barrier dysfunction and commensal imbalance. In turn, the dysbiotic microbiome triggers a regenerative response and stimulates tumor growth. We find that inhibiting JNK signaling or depletion of the microbiome restores barrier function of the intestinal epithelium, leading to a reestablishment of host-microbe homeostasis, and organismic lifespan extension. Our experiments identify a JNK-dependent feedback amplification loop between intestinal tumors and the microbiome. They also highlight the importance of controlling the activity level of JNK signaling to maintain epithelial barrier function and host-microbe homeostasis.
Gesehen am 04.06.2020